New and potential properties, characteristics, and analytical methods of ferulic acid: A review - Danieli Camilo Marcato; Caroline Magnani Spagnol; Hérida Regina Nunes Salgado; Vera Lucia Borges Isaac; Marcos Antonio Corrêa (Universidade de São Paulo, 2022)
Abstract Phenolic compounds are widely distributed in the plant kingdom and in the microorganisms. Cinnamic acid and its hydroxylated derivative-ferulic acid, are phenolic compounds. Ferulic acid possesses antioxidant potential, as well as anti-cancer, anti-inflammatory, and antimicrobial properties. It prevents the harmful effects of radiation both as an ultraviolet absorber and as a free radical scavenger; it is not cytotoxic. Although ferulic acid has beneficial properties, it is hardly used in cosmetic preparations and has been rarely studied in the literature. Herein, we review the literature on ferulic acid, to provide information which can contribute to further research on the compound.